PRINSIP DAN TEKNIK MENGAJARKAN KOSAKATA BI KEPADA PEBELAJAR BIPA - Susanto, Gatut (Diksi, 2007)
The extent of vocabulary possessed by learners of BIPA, of BahasaIndonesia sebagai Penutur Asing, or of the Indonesian language as foreignspeakers, has a positive correlation with the extent of their achievement inmastering that language. As part of the effort to keep applying communicativeteaching, careful attention needs to be paid to the teaching of vocabulary tolearners of BIPA in order that it remains on the communicative lane and thevocabulary learned has enduring retention in their memory so that they could makeit function both as a means of communication and as a means of performing theirspeech acts.The syllabus planned for the vocabulary teaching is a curriculum modeldetermining the direction of the teaching program and describes the objectives tobe achieved in each learning activity. The syllabus design enables the teachers toformulate lesson plans that are in line with the teaching objectives to be achieved.The plan of the syllabus should be made integrally in order that the vocabularyteaching could be linked with other components like skill aspects of the targetlanguage such as function, context, and grammar as well as its cultural aspects.Keywords: vocabulary, foreign speakers, teaching